The "Down the PC" view – A new tool to assess screw positioning in the posterior column of the acetabulum. Issue 8 (August 2015) - Osterhoff, G.; Amiri, S.; Unno, F.; Dodd, A.; Guy, P.; O'Brien, P.J.; Lefaivre, K.A.
Abstract Introduction Minimal-invasive placement of screws into the posterior column of the acetabulum (PC) is challenging. Due to the saddle-shaped curvature of the medial cortical border of the PC, the standard fluoroscopic views of the pelvis cannot provide the desired safety during screw insertion. The aim of this study was to define a view tangentially to the medial cortex of the PC and to evaluate its accuracy and inter-observer reproducibility. Methods Radio-dense markers on the medial cortex of the PC along the axis of a PC screw were brought in line and landmarks of the new "Down the PC" view were determined. Kirschner wires were placed into the PC of a pelvis composite model and five pelvic cadaver specimens in a total of 34 different correct and incorrect positions. Based on either only the "Down the PC" view, only the standard views, or a combination of both, three fellowship-trained orthopaedic surgeons had to decide if the inserted wires were in bone in the posterior column or had exited cortex, and if they penetrated the acetabulum. Sensitivity, specificity, and the intra-class correlation coefficient were calculated. Results A view using three radiographic landmarks (pelvic brim, medial cortical wall of the body of the ischium, ischial spine) was found. Sensitivity and specificity to detect perforation out of the bone were 1.00 and 0.97 for the "Down the PC" view, 0.46 and 0.97 if only the standard views were used, and 1.00 and 0.95 for a combination of both. Sensitivity and specificity to detect intra-articular wire placement were 1.00 and 0.96 for the "Down the PC" view, 0.72 and 0.95 if only the standard views were used, and 0.94 and 0.99 for a combination of both. Inter-observer agreement using only the "Down the PC" view was excellent with an ICC of 0.92 for perforation and ICC of 0.82 for intra-articular wire placement. Conclusions The "Down the PC" view is a useful addendum in the orthopaedic trauma surgeon's tool box. Using simple landmarks, it is easily to reproduce and thereby shows excellent accuracy and inter-observer agreement in order to detect medial perforation or intra-articular implant position.